1991
DOI: 10.1152/ajpheart.1991.260.2.h327
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet aggregation and shape change are coupled to separate thromboxane A2-prostaglandin H2 receptors

Abstract: The relationships of human platelet thromboxane A2-prostaglandin H2 (TxA2/PGH2) receptor occupation as assessed by equilibrium binding of the TxA2/PGH2 agonist [125I]BOP to the functional responses of I-BOP-induced platelet shape change and aggregation were determined before and after specific, irreversible inactivation of platelet TxA2/PGH2 receptors with the photolyzable TxA2/PGH2 antagonist I-PTA-PON3. I-BOP stimulated platelet shape change and aggregation with concentrations producing a half-maximal respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Low concentrations of I-BOP (Յ0.3 nM) that induced only shape change in the absence of platelet aggregation (32,34) failed to phosphorylate pleckstrin or induce aggregation (Fig. 2B).…”
Section: Resultsmentioning
confidence: 96%
“…Low concentrations of I-BOP (Յ0.3 nM) that induced only shape change in the absence of platelet aggregation (32,34) failed to phosphorylate pleckstrin or induce aggregation (Fig. 2B).…”
Section: Resultsmentioning
confidence: 96%
“…Some studies using the radiolabeled TXA 2 analogs as ligands demonstrated two classes of binding sites in platelets, and indicated that they might represent the receptor subtypes (5)(6)(7)(8). They further suggested that the two putative subtypes of the receptor may independently mediate shape change and aggregation (8,9). This suggestion has been supported by the reports that platelet shape change and aggregation can be differentiated by several TXA 2 analogs.…”
Section: Introductionmentioning
confidence: 88%
“…The K d values correspond to the EC 50 values for I-BOP to induce shape change and aggregation. Thus, the binding of I-BOP to low affinity receptors induces secretion and aggregation, whereas its binding to high affinity receptors induces shape change (8). Similarly, a TP antagonist such as GR 32191 shows noncompetitive inhibition of platelet aggregation but competitive inhibition of platelet shape change, consistent with the existence of two subtypes of receptors (9).…”
mentioning
confidence: 90%
“…Evidence suggests that two different TPs within the platelets or two different affinity states of the same receptor may exist. Analysis of the binding of 125 I-labeled I-BOP by platelet membranes indicates two platelet binding sites of high affinity (K d ϭ 270 Ϯ 60 pM) and low affinity (K d ϭ 3.9 Ϯ 1-2 nM) (8). The K d values correspond to the EC 50 values for I-BOP to induce shape change and aggregation.…”
mentioning
confidence: 99%